Long-Term Balance Outcomes in Vestibular Ablative Surgeries - Fakih Cihat Eravcı; Metin Yılmaz; Ebru Şansal; Nagihan Gülhan; Recep Karamert; Hakan Tutar; Mehmet Birol Uğur (Turkish Archives of Otorhinolaryngology, 2021)

(untitled)
Objective:To evaluate the long-term balance outcomes of vestibular nerve section (VNS) and labyrinthectomy (L) operations. The indirect outcomes will be the correlation of objective and subjective test results and an analysis of anterior-posterior versus medial-lateral computerized posturography (CP) scores.Methods:This retrospective study evaluated objective CP and subjective Dizziness Handicap Inventory (DHI) results of patients who underwent VNS and L surgeries for Ménière’s disease.Results:A total of 55 (31 VNS and 24 L) patients were included in the study. The two operation groups were similar in terms of age, and mean time between surgery and the tests (p=0.465 and p=0.616) respectively. The vestibular and global scores at anterior-posterior CP showed statistically significant differences between the groups (p=0.000 and p=0.007) respectively in favor of the VNS group. In addition, the comparison of the vestibular CP scores of anterior-posterior and medial-lateral evaluations of the entire study population was lower in the medial-lateral evaluation (p=0.000). The mean DHI scores did not show statistically significant differences (p=0.359) between operation groups, nor did the correlation analysis between CP and DHI scores reveal statistical significance (p values >0.05).Conclusion:In the long term, objective balance outcomes are better for VNS patients than for L patients. Additionally, medial-lateral balance outcomes are more affected than anterior-posterior balance outcomes from unilateral ablative surgeries. Subjective balance perception is not different between the two surgery groups, and DHI scores do not show a correlation with CP scores.